Determination of ATC and security for power system using A1 technique - Abdul Gani, Ahmad Zhafri (2011)
Available Transfer Capability (ATC) has recently gained the interest of power industry and deregulated environment. To achieve efficiency and precision in utility operation, the determination and calculation of ATC are important. There are many technical challenges that are involved in computing ATC values. This includes the total transfer capability calculation, transmission capability margins and probabilistic ATC calculation. In power system deregulation, the Independent System Operator (ISO) is responsible to control the power transactions and also to avoid overloading of the transmission lines beyond their thermal limits. The ISO has to determine the ATC index periodically in real time to enable market participants to reserve the transmission service. To test the performance of the methodologies and programs for IEEE-30 bus system, the proposed computation procedure of ATC with margins using conventional technique has been developed . The results have been compared with a developed fuzzy model using the data sets that are not used for training purpose. The data set, line number and the relative error have been recorded for analysis. The results suggest that ATC can be accurately estimated by using fuzzy logic for various load levels.